Potential of attractive toxic sugar baits for controlling Musca domestica L., Drosophila melanogaster Meigen, and Megaselia scalaris Loew adult flies - Wongthangsiri, Denphum; Pereira, Roberto M.; Bangs, Michael J.; Koehler, Philip G.; Chareonviriyaphap, Theeraphap (Agriculture and Natural Resources, 2018)
Musca domestica, Drosophila melanogaster and Megaselia scalaris (Diptera: Muscidae, Drosophilidae, and Phoridae, respectively) are common urban pest flies. Potential control of these adult fly species using an attractive toxic sugar bait (ATSB) system was evaluated in the laboratory. ATSB, consisting of a combination of mango fruit syrup (as bait) and acetamiprid (as toxic agent), was evaluated and compared with a commercially available fly bait (EndZone™ Insecticide sticker, FMC Corp., USA) containing acetamiprid. Mango syrup without toxicant (ASB) served as the negative control. The ASB + acetamiprid bait was the most effective control mixture based on initial knockdown within 10 min for house flies and 200 min for phorids. The combination produced a higher percentage of mortality in house flies and phorids, respectively, than in fruit flies; however, there was no significant difference between the bait formulations as indicated by the mean mortality of house flies and phorids. Significant differences in Drosophila mean mortality were demonstrated between the ATSB combinations. These findings suggested a fruitbased ASB + acetamiprid system could be used as a cost-effective, alternative for adult fly control.